OPTIMIZATION OF VILLAGE INFORMATION SYSTEMS IN VILLAGE INFORMATION DISCLOSURE IN MASAWAH VILLAGE, CIMERAK DISTRICT, PANGANDARAN REGENCY - Indra Taufiqqurrahman; Irfan Nursetiawan (Faculty of Social And Political Science Universitas Galuh, 2021)
The era of technology makes it easier to do an activity and change a job to be easier. This is inseparable from the implementation of village governance in Masawah Village, Cimerak District, Pangandaran Regency. This is by Law Number 6 of 2014 Article 86 paragraph 4 which mandates that the Village Information System contains information covering village data, village development, rural areas, as well as other information related to village development and rural area development. Likewise, what happened in Masawah Village, Cimerak District, Pangandaran Regency which became a new autonomous region that made the Village Information System a means of administering village government by utilizing the Village Information System. However, in practice, the Masawah Village Government has not been able to optimize the existing Village Information System as an effort to provide public information disclosure and public services easily and quickly. The method used in this study is a qualitative descriptive method. The results showed that the optimization of the Village Information System in Public Information Disclosure in Masawah Village, Cimerak District, Pangandaran Regency was still not running optimally, this was because there were still many obstacles experienced by the Masawah Village government, Cimerak District, Pangandaran Regency in optimizing the Village Information System, such as Source Human Resources, Infrastructure, and Technology Readiness in Masawah Village, Cimerak District, Pangandaran Regency.